Acid Violet 17: a New Dye for Chromovitrectomy? - Gerding, H. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background: Acid violet 17 (AV17) has recently received CE certification as a dye for intraocular use during vitreoretinal interventions. This publication reviews the available preclinical and clinical data on the use of this new dye. Material and Methods: A systematic MEDLINE literature search was conducted on preclinical testing, clinical testing, and application of AV17 in ocular cell cultures, organ cultures, or ex vivo and in vivo ocular surgical procedures. Results: Of the 59 primary hits, 5 publications (4 preclinical, 1 clinical) were identified as reporting relevant data. All available results on preclinical testing referred to concentrations of AV17 much lower (0.005 to 1.0 mg/ml) than the presently marketed dye (1.5 mg/ml, ala purple, ala®medics, Dornstadt/Germany). Toxic or undesired effects of AV17 on different ocular structures or cells were observed under the following conditions: retinal pigment epithelium: 0.25 mg/ml, 180 seconds, 0.05 mg/ml, 1800 seconds; ganglion cell viability: 0.25 mg/ml, 30 seconds; Müller cell activation: 0.25 mg/ml, 30 seconds; astrocyte activation 0.5 mg/ml, 30 seconds; microglia activation: 0.5 mg/ml, 300 seconds. No adverse effects were observed in a clinical case series of macular hole surgery (Peel et al. 2015). In this series, the dye was not applied as described in the label. In our own clinical experience, two different undesired effects were observed: transient discolouration of hydrophilic intraocular lenses and degeneration of the RPE in cases of macular hole surgery. Conclusions: Preclinical tests indicate that AV17 has toxic and undesired effects at concentrations much lower than claimed by suppliers. Against the background of these data and the first observations of adverse clinical effects, it seems advisable to be cautious when using AV17.
Keywords: acid violet 17; Coomassie violet R200; chromovitrectomy; intraocular dye; ILM staining; internal limiting membrane; macular hole; macular pucker